Adaptive trajectory tracking control for remotely operated vehicles considering thruster dynamics and saturation constraints. (May 2020) - Chu, Zhenzhong; Xiang, Xianbo; Zhu, Daqi; Luo, Chaomin; Xie, De
Abstract: This paper discusses the problem of adaptive trajectory tracking control for remotely operated vehicles (ROVs). Considering thruster dynamics, a third-order state space equation is used to describe the dynamic model of ROVs. For the problem of unknown dynamics and partially known input gain, an adaptive sliding mode control design scheme based on RBF neural networks is developed using a backstepping design technique. Because of the saturation constraints of the thrusters, a first-order auxiliary state system is applied, and subsequently, a saturation factor is constructed for designing adaptive laws to ensure the stability of the adaptive trajectory tracking system when the thrusters are saturated. The proposed controller guaranteed that trajectory tracking errors are uniformly ultimately bounded (UUD). Finally, the effectiveness of the proposed controller is verified by simulations. Highlights: The thruster dynamics and saturation constraints were considered in controller design. A third-order state space equation was constructed to describe the dynamic of ROVs. The unknown dynamics and partially known gain were considered in controller design. A saturation factor was constructed for the design of the adaptive laws.